AN EVALUATION APPROACH FOR ELIMINATING THE FAILURE EFFECT IN GAS TURBINE USING FUZZY MULTIPLE CRITERIA - Balin, A.; Demirel, H.; Alarcin, F. (ROYAL INST NAVAL ARCHITECTS, 2016)
This paper demonstrated the fuzzy AHP combined with fuzzy VIKOR technique integrated with essentials of weight in order to overcome the risk evaluation process of the uncertainty in subjective perception and experience of human. Gas turbine has considerably expanded its role in several areas subsequent to the improvement in high efficiency and clean energy such as aviation and marine propulsion systems, electric power stations, and natural gas and petroleum transportation. However, the cost of various industrial plants and their relevant maintenance appear to be extremely expensive to be operated by these gas turbines. This paper aimed to cope with the essential elements of gas turbine including hydraulic-pneumatic equipment, electronic control equipment, and bearing equipment. The results have proved the bearing equipment to have been the most effected alternative, as being ensued by hydraulic-pneumatic equipment and electronic control equipment.
Keywords: EXTENDED VIKOR METHOD; ANALYTIC HIERARCHY PROCESS; GROUP DECISION-MAKING; HYBRID MCDM MODEL; CUSTOMER SATISFACTION; COMPROMISE SOLUTION; MATERIAL SELECTION; AHP; ENVIRONMENT; ISTANBUL; Engineering